Predator-Induced Plasticity on Warning Signal and Larval Life-History Traits of the Aposematic Wood Tiger Moth, Arctia plantaginis - Almeida, Diana Abondano; Mappes, Johanna; Gordon, Swanne (Frontiers in Ecology and Evolution, 2021)
Predator-induced plasticity in life-history and antipredator traits during the larval period has been extensively studied in organisms with complex life-histories. However, it is unclear whether different levels of predation could induce warning signals in aposematic organisms. Here, we investigated whether predator-simulated handling affects warning coloration and life-history traits in the aposematic wood tiger moth larva, Arctia plantaginis. As juveniles, a larger orange patch on an otherwise black body signifies a more efficient warning signal against predators but this comes at the costs of conspicuousness and thermoregulation. Given this, one would expect that an increase in predation risk would induce flexible expression of the orange patch. Prior research in this system points to plastic effects being important as a response to environmental changes for life history traits, but we had yet to assess whether this was the case for predation risk, a key driver of this species evolution. Using a full-sib rearing design, in which individuals were reared in the presence and absence of a non-lethal simulated bird attack, we evaluated flexible responses of warning signal size (number of orange segments), growth, molting events, and development time in wood tiger moths. All measured traits except development time showed a significant response to predation. Larvae from the predation treatment developed a more melanized warning signal (smaller orange patch), reached a smaller body size, and molted more often. Our results suggest plasticity is indeed important in aposematic organisms, but in this case may be complicated by the trade-off between costly pigmentation and other life-history traits.